Perfil do desenvolvimento motor de lactentes com síndrome de Down dos 3 aos 12 meses de idade - Pereira, Karina (2008)
This study aimed to characterize and identify the rate of motor development in both infants with Down syndrome (experimental group) and typical infants (control group) at the age range of 3-12 months. The infants were assessed in terms of motor performance, motor acquisition, minimum and maximum age to acquire a motor skill, and maximum age to acquire all the skills composing each positional scale (prone, supine, sitting and standing). Three papers and one chapter of a book were written to deal with these issues. The Alberta Infant Motor Scale (AIMS) was used for data collection. In paper 1, the rate of motor development in typical infants increased over the months in all body positions. Significant motor performance was observed at 3 and 6 months for the girls, and at 12 months for the boys. There was no relationship of weight and length, whether at birth or over age, with the infants motor development. In paper II, the experimental group showed an increasing but slow rate of motor development from 3 to 12 months. In paper III, motor performance was lower in infants of the experimental group. These infants took one to four months more to acquire motor skills when compared to control group. In the chapter of the book, examples of how to handle infants emphasized neuro-sensorymotor stimuli in different body positions with the aim of instructing caregivers on how to stimulate their child to interact, explore and learn about the environment in a more functional and independent manner. The results indicated that motor development was increased in infants with Down syndrome, following the same sequence of motor acquisitions as the typical infants. However, the rate was slower for the infants with Down syndrome, especially in prone, sitting and standing positions in which they were unable to perform all the skills. Furthermore, the infants with Down syndrome took more time to acquire a new skill. These studies fill the gap in the knowledge about the process of motor development as well as about the identification of motor milestones in infants with Down syndrome under physiotherapy intervention. In this sense, this research allows therapists to properly identify and assess infants with Down syndrome, thus contributing towards both the planning of therapeutic intervention and the development of guidelines aimed at instructing caregivers on how to prioritize antigravity positions and skills.